2012
DOI: 10.4244/eijv7i12a219
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infarction angina predicts thrombus burden in patients admitted for ST-segment elevation myocardial infarction

Abstract: Absence of PIA and proximal culprit lesions are associated with higher thrombus grade. Higher thrombus grade is associated with larger infarct size and slightly worse LV function. This may have clinical implications in planning strategies, particularly regarding pharmacotherapy, that aim to decrease thrombus burden prior to stent implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
6
15
1
Order By: Relevance
“…But as thrombus usually propagates proximally, this can also complicate determining the initial site of thrombus formation. As reported previously in de novo lesion STEMI, a high thrombus grade is more often seen with reduced initial TIMI 3 flow and the same finding was observed in this study with ST. Glycoprotein IIb/IIIa inhibitors were administered more often to patients with high thrombus burden, likely due to operator recognition of the requirement for potent and immediate antiplatelet therapy. A large thrombus burden during de novo STEMI treated with PCI is associated with an increased risk of future ST and correlates with worse outcomes .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But as thrombus usually propagates proximally, this can also complicate determining the initial site of thrombus formation. As reported previously in de novo lesion STEMI, a high thrombus grade is more often seen with reduced initial TIMI 3 flow and the same finding was observed in this study with ST. Glycoprotein IIb/IIIa inhibitors were administered more often to patients with high thrombus burden, likely due to operator recognition of the requirement for potent and immediate antiplatelet therapy. A large thrombus burden during de novo STEMI treated with PCI is associated with an increased risk of future ST and correlates with worse outcomes .…”
Section: Discussionsupporting
confidence: 92%
“…This may be related to different mechanisms between early, late, and very late ST . A higher thrombus grade was also seen in the more distal vessel segments, in contrast to a recent report of a proximal vessel location being an independent predictor of high thrombus grade in STEMI involving native vessel coronary artery disease . However the mechanisms of ST differ from that of de novo plaque rupture leading to STEMI.…”
Section: Discussioncontrasting
confidence: 57%
“…Another interesting finding of our study was that preinfarction angina was associated with lower thrombus burden among patients with angiographic thrombus, although the overall incidence of angiographic thrombus was similar between the 2 groups. The association between preinfarction angina and lower thrombus burden has also been demonstrated in the STEMI population . This association was consistent with that in a previous study that demonstrated that the culprit plaques of patients with preinfarction angina had less necrotic core component, which has been shown to be the most thrombogenic component in human atherosclerotic plaques, than those of patients without preinfarction angina.…”
Section: Discussionsupporting
confidence: 90%
“…In an animal model, they observed that brief, nonlethal episodes of ischemia before a more sustained ischemic insult reduced infarct size depending on the duration of ischemia. In the PPCI era, some retrospective analyses failed to show benefits of PIA for major adverse events [11] or infarct size [9], whereas others showed benefits in terms of lower infarct size, lower thrombus grade, and better left ventricle function [12]. In the PPCI era, some retrospective analyses failed to show benefits of PIA for major adverse events [11] or infarct size [9], whereas others showed benefits in terms of lower infarct size, lower thrombus grade, and better left ventricle function [12].…”
Section: Cardioprotection and Preinfarction Anginamentioning
confidence: 99%
“…This has led to huge interest in the field of cardioprotection to overcome the so-called reperfusion-injury phenomenon [2][3][4][5][6][7]. Nevertheless, the effect of PIA in the era of PPCI has yielded mixed results [9][10][11][12][13]. Nevertheless, the effect of PIA in the era of PPCI has yielded mixed results [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%